Pengaruh Jiwa Kewirausahaan Kepala Madrasah Terhadap Jiwa Kewirausahaan Siswa - Heri Hoerudin; Kun Nurachadijat (Universitas Katolik Widya Karya Malang, 2023)
This study aimed to determine the effect of Islamic School (Madrasah) Principals’ entrepreneurship on Students’ entrepreneurship in the Islamic School Education environment. Entrepreneurship among students is an essential factor in creating a personality that is equipped to encounter workplace challenges and create opportunities in various sectors. Principals play a crucial role in shaping a school culture that promotes and facilitates the entrepreneurial development of students as educational leaders. This research employed a qualitative approach through interviews and observations as a data. The respondents of the study were the Islamic School Principals and students of Madrasah Aliyah in Soreang District, Bandung Regency. The study’s findings demonstrated that the entrepreneurship of Islamic School Principals significantly affected students’ entrepreneurship. Islamic School Principals with a high spirit of entrepreneurship could serve as role models who inspire students to adopt proactive, innovative, and independent attitudes. Essential factors that encourage the development of student entrepreneurship include a learning environment that promotes entrepreneurship and empowers students, a relevant curriculum, and entrepreneurial attitudes. This study provided a deeper comprehension of the significance of the role of the Islamic School Principal in shaping student entrepreneurship. The practical significance of this research is the necessity to establish educational policies that emphasise developing student entrepreneurship in the context of the Islamic School environment. Thus, this research can enhance educational quality and equip students for increasingly complex and competitive business and entrepreneurship challenges in the future.